Create and Sustain Competitive Advantage in Online/IT industry - Jukelsonová, Sofie; Jaklová, Martina L.; Butor, Pauline; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2012)
The purpose of this work is to define a theorical framework to explain sustainability of competitive advantage in what we will name network industries: social networks, internet based services, mobile devices and online softwares. This framework will consist in integration of the well known Porter approach combined with a more recent Resource Based View of the firm. Using four real cases, with a focus on Google, we will demonstrate that sustaining competitive advantage in those industries requires a combination of external opportunities and a strong defensible resource position. One without the other cannot lead to long term success. In order to make our conclusions actionable, we will lay down a checklist of strategic diagnosis that any decision maker in that industry should have in mind at all time, in order to defend his / her market share.
Vedoucí práce: Martina L. Jaklová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2012
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2012
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses